Community Health Improvement: Social Care Is Healthcare. Issue 2 (2022) - Kryzer, Emily; Nolan, Christopher M.
Abstract : Like many communities across the United States, St. Louis, Missouri, faces stark inequities in health outcomes, including wellness, quality of life, and life expectancy. These inequities are the result of social systems and policies that have robbed generations of St. Louisans of opportunity. BJC HealthCare's (BJC's) commitment to becoming a catalyst for community health by helping to eliminate health disparities led to the launch of its community health improvement strategy. This article details the community-driven and evidence-informed process that BJC used to create a multiyear, proactive approach to addressing the social and economic factors that are the root causes of health inequities. It examines areas of opportunity through which the strategy will drive change and explores lessons learned and promising practices for other healthcare institutions to consider as they advance health equity.